Russia's spectacle of "traditional values": rethinking the politics of visibility. Issue 1 (1st January 2020) - Edenborg, Emil
ABSTRACT: This article examines the role of visibility in efforts to define "the people" in specifically gendered and sexualized ways. In doing this, it contributes to queer and feminist international relations (IR) scholarship, where visibility and invisibility, although central themes, are sometimes insufficiently problematized. In a case study of Russia's contemporary project of "traditional values, " I show how the Kremlin-promoted heteropatriarchal definition of community relates to efforts to control the visibility of gendered and sexualized bodies, and how those regulations are resisted, with respect to queer visibility, on the one hand, and patriotic military visibility, on the other. I argue: (1) that efforts by states to define and delineate "the people, " involve the production of arrangements of visibility, regulating what gendered, sexualized, and racialized bodies can appear in public, and how they are seen; and (2) that those who resist hegemonic conceptions of community seek to disturb and reorder those arrangements of visibility, by making visible bodies that have been rendered invisible or making already present bodies visible in new ways. However, such forms of embodied appearance will not necessarily come in the form of antithetical opposition, but may be more ambivalent.